Psychometric Properties of the Spanish Version of the Caregiver Contribution to Self-Care of Diabetes Inventory (CC-SCODI) - Jesús Martínez-Tofé; Iván Santolalla-Arnedo; Vicente Gea-Caballero; Angela Durante; Antonio Martínez-Sabater; Mercedes Sánchez-Barba; Marco Di Nitto; Pilar Sanchez-Conde; Silvia Gónzalez-Fernández; Regina Ruíz de Viñaspre-Hernández; Raúl Juárez-Vela; Nelia Soto-Ruiz (Nursing Reports)
Background: The Caregiver Contribution to Self-Care of Diabetes Inventory (CC-SCODI) is an instrument grounded in the middle-range theory of self-care of chronic illness. It is designed to measure how caregivers support individuals with diabetes mellitus in carrying out self-care activities. Effective tools are essential for clinicians and researchers to evaluate factors influencing self-care, including caregivers’ contributions. This study aimed to assess the reliability and validity of the Spanish translation of the CC-SCODI. Methods: A total of 201 caregivers of individuals with Type 1 Diabetes Mellitus (T1DM) and Type 2 Diabetes Mellitus (T2DM) were recruited for participation in this cross-sectional study. Participants were selected through convenience sampling at a university hospital. Before administration, the survey questions were translated and culturally adapted to ensure appropriateness for both patients and caregivers. Confirmatory factor analysis (CFA) was performed on each of the CC-SCODI subscales using models fitted to the relevant indices. Results: The initial construction of the four-dimensional tool was verified. The internal consistency of the four subscales was assessed using Cronbach’s α to measure the caregiver contribution to patients’ self-care maintenance (α = 0.725), self-care monitoring (α = 0.728), self-care management (α = 0.729), and caregiver self-efficacy in contributing to patient self-care (α = 0.921). Model fit indices demonstrated a chi-square value of 1.028 with 773 degrees of freedom. CFA indicated an excellent model fit, confirming the reliability and validity of the proposed structure. Conclusions: The internal consistency and reliability of the Spanish version of the CC-SCODI were deemed adequate. Due to its strong psychometric properties, this instrument is considered appropriate for evaluating the contribution of caregivers to the self-care behaviors of Spanish-speaking individuals with diabetes.